2022
DOI: 10.3390/educsci12090627
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-19 Transition in University Physics Courses: A Case of Study in a Mexican University

Abstract: The extended confinement imposed by the COVID-19 pandemic lockdowns resulted in the imposition of online education for two years. Many students experienced their transitions to higher educative levels during this time, surely losing some academic learning as a consequence. On the other hand, this context could have promoted different types of competencies, until recently not explored, as a function of students’ personalities or academic profiles. Physics teaching is among those areas which have changed from it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…Personality can be defined as a symbolic characteristic that relates to the potential for activity in each individual. It presents itself as a brand image that differentiates individuals based on how they react to emerging events [1]. Several studies indicate that the COVID-19 pandemic has had a significant impact, albeit temporary, on the personality profile, well-being, and educational performance of secondary school students.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Personality can be defined as a symbolic characteristic that relates to the potential for activity in each individual. It presents itself as a brand image that differentiates individuals based on how they react to emerging events [1]. Several studies indicate that the COVID-19 pandemic has had a significant impact, albeit temporary, on the personality profile, well-being, and educational performance of secondary school students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Education systems at various levels have undergone significant changes due to the global calamity caused by the recent COVID-19 pandemic. Although education systems vary from country to country, the period corresponding to the pandemic has had and will continue to have a significant impact on education and future generations for many years [1].…”
Section: Introductionmentioning
confidence: 99%
“…A recent poll revealed that 75% of educators believe digital content will replace textbooks by 2026. Choosing which innovations to bring into the classroom is somewhat of a challenge [2,16]. Students must use many cognitive, motivational, behavioral, and contextual components to be successful in digital learning.…”
Section: Different Future Students Different Future Needsmentioning
confidence: 99%
“…However, the rapid return to face-to-face teaching and learning and the stabilization of enrollment patterns suggest that the changes will only lead to a partial transformation of higher education as a face-to-face experience. Thus, higher education institutions may introduce some necessary new procedures long-term (Delgado, 2022, Marinoni et al, 2020, Plakhotnik, M. S. et al 2021. We can ask whether university students will be sufficiently prepared for a professional career in continuity with the market's and society's needs?…”
Section: Introductionmentioning
confidence: 99%